2010
DOI: 10.1002/ppul.21270
|View full text |Cite
|
Sign up to set email alerts
|

Serum SP‐D levels as a biomarker of lung injury in respiratory syncytial virus bronchiolitis

Abstract: To evaluate whether SP-D concentration is a useful biomarker of the severity of respiratory syncytial virus (RSV) bronchiolitis, we determined SP-D concentrations in patients with RSV bronchiolitis with or without chronic heart disease. We enrolled 52 patients who had been diagnosed with RSV bronchiolitis and required admission to the hospital at the Department of Pediatrics of Fukushima Medical University School of Medicine from 2004 through 2005. These patients were divided into two groups: Group 1 consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 13 publications
3
15
1
Order By: Relevance
“…It causes lung tissue [19]. Serum SP-D has been identified as potential biomarker for some pulmonary disease, such as respiratory syncytial virus bronchiolitis [20], idiopathic interstitial fibrosis [21], acute respiratory distress syndrome [22] and allergic broncho pulmonary aspergillosis [23]. In our study, we found significantly increased levels of SP-D in patients with smoker COPD and in patients with non-smoker COPD as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 63%
“…It causes lung tissue [19]. Serum SP-D has been identified as potential biomarker for some pulmonary disease, such as respiratory syncytial virus bronchiolitis [20], idiopathic interstitial fibrosis [21], acute respiratory distress syndrome [22] and allergic broncho pulmonary aspergillosis [23]. In our study, we found significantly increased levels of SP-D in patients with smoker COPD and in patients with non-smoker COPD as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, circulating SP‐D is known to primarily reflect alveolar permeability due to lung inflammation (Hartl and Griese 2006). Serum SP‐D concentration was found in human subjects to be related to severity of respiratory disease (Kawasaki et al . 2011) and clinical outcome (Eisner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Human adenovirus can also alter surfactant phospholipid composition [61], whereas Aspergillus fumigatus and Pneumocystis carinii can downregulate SP-B and SP-C protein and mRNA expression [1]. In some studies, pathogens induce expression of collectins [6567]. …”
Section: Role Of Infection On Surfactant Compositionmentioning
confidence: 99%